New family code of Slovenia (2017): procedural aspect - KraljiÄ‡, Suzana (2018)
Slovenia went in past years through turbolent time in the field of family law: new definitions or redefinitions of marriage have been presented, topics related to the parenthood have undergone changes, the adoption has been the subject of many discussions, there have been two referendums related to same-sex partnerships… Finally, March 23 April 2017, new Family Code was adopted. One of the important changes, brought by the Family Code, are related to jurisdictions in family matters, which have been transferred from administrative bodies to the courts. The aim of this transfer is raise the procedural protection of children. In doing so, the legislator followed the request, that the jurisdictions for substantively similar issues should not be proceed by the different authorities. Due this, the jurisdiction on adoption, foster care and guardianship is transferred to the courts. But there is also a two-track system, in which the family matters could be handled in civil or non-contentious procedures. Regardless of the procedure (administrative, civil, non-contentious), the best interest of the child shall be a primary consideration. Therefore, the Family Code gives special intention also on child protective measures, which represents the obligation of the state to protect the child’s best interests. Child’s interest” is a legal standard, which value has to be made concrete by respecting all circumstances of a single case. Therefore, the courts have to provide proper procedural safeguards, despite of the type of procedures.